THE IMPORTANCE-PERFORMANCE ANALYSIS OF SERVICE QUALITY AT AQUARIUS CAR WASH - Pijoh, Hannah Nadia; Lambey, Linda (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Transportation plays a vital role in the community. It has started to strive to be considered as primary needs. In recent year, it can be seen there is a significant increase in the number of vehicles sold. It becomes an opportunity for entrepreneurs to run such business in car wash services. With the high demand of vehicles purchased and a lot of customers do not have much time to wash their car. Entrepreneurs should give good service and create customers? satisfaction. In addition to provide outstanding services, entrepreneurs need to evaluate their service in order to improve the quality of their performance. This research aims to analyze the importance-performance analysis of service quality at Aquarius Car Wash. The type of this research is a quantitative descriptive research. The Importance-Performance Analysis was used in this research. The sample of this research is the customer of Aquarius Car Wash consists of 100 respondents. The sample was taken by accidental sampling. The result shows, (1) Timely Completion is located in quadrant I. (2) Car Washing Equipment, Ability to Provide Service, Reasonableness of Costs, Service Meets Customer Expectations, Trustworthiness of Employees, Professionalism of Employees and Vehicle Security Guarantees are located in quadrant II. (3) Employees Appearance, Building Condition, Willingness to Assist Customers, Ability to Resolve Customer Problems, Understanding Special Needs of Customers and Prioritization of Customer Best Interest are located in quadrant III. (4) Personalized Attention from Employees is located in quadrant IV. Aquarius Car Wash should maintain their good service and should improve their low performance. By doing so, it is hoped that their customers will be satisfied and will be their loyal customers. Keywords: service quality, importance-performance analysis, transportation